Effect of Coriaria lactone on cytosolic free calcium of cultured neurons from rat cerebral cortex - Zhu Xiao-Feng; Zhao Xi-Long; Zhu Chang-Geng; Wang Jin-Xi (Acta Pharmacologica Sinica; Vol 19, No 4 (July 1998): Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of Coriaria lactone (CL) on cytosolic free calcium ([Ca2+]i) of cultured neurons from cerebral cortex. METHODS: Primary neuron culture (14d) and AR-CM-MIC cation measurement system were used, the [Ca2+]i were measured. CL effect was observed by loading egtazic acid. RESULTS: The [Ca2+]i of cultured neurons (99.4-103.4) nmol.L-1 was elevated concentration-dependently by CL (25-500) mumol.L-1 (P < 0.01). This effect disappeared after loading egtazic acid 5 mmol.L-1, but reappeared after adding CaCl2 to 1 mmol.L-1. CONCLUSION: The [Ca2+]i of cultured neurons was elevated by CL, depending on extracellular Ca2+.